Financing Higher Education and Economic Development in East Asia - Armstrong, Shiro; Chapman, Bruce (Canberra ANU Press, 2011)
This volume addresses important issues to do with access to higher education and different models of its financing in the East Asia region. It is enriched by diverse perspectives from vastly different starting points and by the historical and institutional settings in the region. The issues are set out in the context of the value of higher education in economic development and how it contributes to the capacities to adopt and adapt to new technologies and undertake institutional innovation. The established and well-functioning higher education loan and financing systems, such as those in Australia, and the experience of different systems tried$1 (Bboth in East Asia and in the United States$1 (Bare brought to bear in this volume.s
English
Keywords: Education; Economics; east asia; economic development; costs; education; Higher education; Indonesia; Private school; Student loan; Subsidy; Tertiary education fees in Australia; Thailand; Tuition payments